FEASIBILITY OF RICE HUSK FOR ELECTRICITY GENERATION: A CASE STUDY AT AVNASH RICE MILL - Kumih, F.; Issahaku, M. (UDS International Journal of Development, 2022)
AbstractThe erratic power supply from the national grid has the potential to decrease the production hours of industries. Climate change is altering rainfall patterns and threatening crop production and food security. Rice factories' process capacity is affected negatively. The Hybrid Optimization for Multiple Energy Resources (HOMER) software used in the study provided the technical and economic modeling to provide power for a rice mill in northern Ghana. A biomass system is considered the optimal system comprising a 1250 kW biogas generator, with a gasification ratio of 0.4, an estimated daily rice husk generation of 50 tonnes/day, and a daily load demand 3689.75kWh/day. The cost of energy (COE) of the proposed system was US$ 0.0703/kWh, with a total net present cost (NPC) of $712,082.00 and initial capital of US$ 437,500.00. The base system which was a 1300kW diesel generator, with NPC of US$ 2.93M, COE of US$ 0.290/kWh, and lower initial investment capital of US$ 186,697.00. The proposed system could generate electricity in a 98,158 kWh/yr surplus, which could power the mill's administrative building with zero unmet loads. Analysis of the system showed that the quantity of rice husk produced at the Avnash mill was sufficient for power generation from a biogas generator at current production. It suggested that the mill could be self-sufficient and contribute significantly to reducing GHG emissions. Keywords: Rice husk, Hybrid system, Sensitivity, Electricity, COE, HOMER